The Broch of Burrian, North Ronaldsay, Orkney - MacGregor, Arthur (Proceedings of the Society of Antiquaries of Scotland, 1975)
HY 763514. The first complete catalogue of the finds also assesses the general significance of the site. Contrary to the excavator's view, all finds must be regarded as unstratified; nonetheless the rich collection of bone and stonework, pottery and metalwork warrants study in its own right. The date range appears to be late 1st century BC to late 8th AD. The bone sample was inadequate for proper assessment of the economy.